Cross-Cultural Competence and Neuroticism Characters to Manage Ethnocentrism with Global-Oriented Leadership as Moderating Variable - Fachrunnisa, Olivia; Mulyaningtyas, Belia (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
In a constantly changing global business environment, multiculturalism and diversity are becoming important discussion topics for ASEAN Economic Community. The purpose of this research was to know how to reduce ethnocentrism expatriates residing in Indonesia. This research presents findings of study of the influences of cross cultural competence, cross cultural experiences, neuroticism characters, and global-oriented leadership to manage the ethnocentrism of expatriates in Indonesia. Global-oriented leadership moderates the influences of cross-cultural competency, and neuroticism as well with the organization development program that will improve the capability of work and decrease the ethnocentrism level of expatriates. Additionally, a multicultural environment encourages diversity and employee involvement as well as creates a sense of ownership and responsibility which are important for managerial to create successful, diverse, and happy workplace. This study concludes that cross cultural competence and neuroticism characters have a negative and significant impact on ethnocentrism, with global-oriented leadership as a moderating variable to reduce ethnocentrism.